2018
DOI: 10.1037/xhp0000502
|View full text |Cite
|
Sign up to set email alerts
|

You ‘have’ to hear this: Using tone of voice to motivate others.

Abstract: The present studies explored the role of prosody in motivating others, and applied selfdetermination theory (Ryan & Deci, 2000) to do so. Initial studies describe patterns of prosody that discriminate motivational speech. Autonomy support was expressed with lower intensity, slower speech rate and less voice energy in both motivationally laden and neutral (but motivationally primed) sentences. In a follow-up study, participants were able to recognize motivational prosody in semantically neutral sentences, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 119 publications
9
53
3
Order By: Relevance
“…As described above, investigators have typically focused on identifying the nature and outcomes of the words speakers select to use when communicating motivation, but new evidence points to the importance of the tone of voice used through which a motivating directive is conveyed. Informed by work on affective prosody (see e.g., Paulmann, 2016, or Mitchell & Ross, 2013, recent work on motivational prosody (Weinstein et al, 2018) has shown that the two motivational qualities of autonomy support and control differ systematically in terms of their acoustic characteristics. Specifically, autonomy-supportive phrasing uses a lower volume and less vocal energy in high frequency bands when compared to intoning controlling phrasing (Weinstein et al, 2018).…”
Section: The Sound Of Motivationmentioning
confidence: 99%
“…As described above, investigators have typically focused on identifying the nature and outcomes of the words speakers select to use when communicating motivation, but new evidence points to the importance of the tone of voice used through which a motivating directive is conveyed. Informed by work on affective prosody (see e.g., Paulmann, 2016, or Mitchell & Ross, 2013, recent work on motivational prosody (Weinstein et al, 2018) has shown that the two motivational qualities of autonomy support and control differ systematically in terms of their acoustic characteristics. Specifically, autonomy-supportive phrasing uses a lower volume and less vocal energy in high frequency bands when compared to intoning controlling phrasing (Weinstein et al, 2018).…”
Section: The Sound Of Motivationmentioning
confidence: 99%
“…Specifically, this procedure allows us to determine if deviance detection for the two motivation qualities differs and which motivation type listeners may attend to preferentially. The only study evaluating the time course of these motivational communications (Zougkou et al, 2018) identified that listening to controlling tones led to more enhanced ERP components (P2, LPP) than either supportive or motivationally neutral tones.…”
Section: The Present Studymentioning
confidence: 99%
“…", which, depending on the tone of voice used by the speaker, could be interpreted in several ways. Past research shows that when spoken with a relatively low pitched, but loud tone of voice, as well as fast speech rate and harsh sounding voice quality, the listener will be driven to action because they are attempting to conform to imposed expectations (Weinstein, Zougkou, & Paulmann, 2018). In contrast, listening to the same message spoken in a higher pitched, quieter tone of voice and a slower speech rate may lead the listener to feel that the action (in this example, to complete a writing task) may be linked to their own interests, beliefs or values (e.g., that writing is a good idea because the author would like to communicate her or his useful findings).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations